Effect of the Mortar Volume Ratio on the Mechanical Behavior of Class CI Fly Ash-Based Geopolymer Concrete - Remigildus Cornelis; Henricus Priyosulityo; Iman Satyarno; Rochmadi .; Iwan Rustendi (Salehan Institute of Higher Education, 2022)
This research described the effect of the mortar volume ratio on the mechanical behavior of Class CI fly ash-based geopolymer concrete. The absolute volume ratio parameters were designed to determine the effects on the mechanical properties of the geopolymer concrete. The volume ratio of the mortar to coarse aggregate voids (Rc) was increased by 0.25 increments, from 1 to 1.75, using constant parameters of 10 M NaOH at a ratio of Na2SiO3to NaOH (R). Furthermore, the alkaline to fly ash ratio (A) of 0.35 and the volume ratio of paste to fine aggregate voids (Rm) of 1.5 were based on geopolymer paste and mortar investigations previously published. The test results showed that 1) the Rc ratio influences the workability and compressive strength of geopolymer concrete; 2) the increase in the Rc ratio by 1.75 is not linear with the rise in compressive strength but produces better mechanical properties; 3) it does not affect the tensile strength of both geopolymer and OPC concretes; 4) the lower the Rc ratio, the higher the flexural strength; 5) the Rc ratio does not affect the OPC concrete and GC tensile strength; 6) the bond stress in geopolymer concrete with an Rc ratio of 1.75 is higher than in OPC concrete; and 7) Rc ratio does not affect the early strength of geopolymer concrete. The geopolymer concrete experienced an increase in compressive strength after 28 days, while the OPC concrete remained flat. The results will help develop an optimal mix design of Class CI ﬂy ash with moderate calcium oxide in the production of geopolymer concrete. This will improve the future applications of using this process in new binding materials. Doi: 10.28991/CEJ-2022-08-09-012 Full Text: PDF